Pelatihan Pemanfaatan Aplikasi Platform Open Course Berbasis Moodle Dalam Mengelola Pembelajaran Daring - Asmiyunda Asmiyunda; Aulia Sanova; Firdiawan Ekaputra (Jurnal Pengabdian UNDIKMA, 2023)
This service activity aims to increase teacher competence and creativity regarding digital classroom management innovations using Moodle-based LMS. This community service was conducted through training, guidance, and evaluation activities with methods in the form of presentations, demonstrations, practices, and discussions. This service partner was SMAN 11 Muaro Jambi. The data collection instrument was a questionnaire which was analyzed descriptively and qualitatively. The results of this service showed that creating a digital learning media platform in the form of a Moodle-based LMS and the average user response through the distribution of questionnaires led that training activities being considered very good and helpful for increasing teacher competence and creativity.